(untitled) (Interdisciplinary Studies Journal, 2023)
Today’s social programs have promoted a substantial strengthening of housing services, as well as a considerable increase in economic development in the country. The present work intends to reflect the relationship between the housing programs, especially Minha Casa, Minha Vida (MCMV), with the productive chain of civil construction, when considering the historical retrospect of the national urbanization process, under the social, economic and social aspects. cool. The methodology used, considering the procedures, takes place through a bibliographic review and documentary research. Economic and social data reveal that the link between housing programs and civil construction reaches all the links in its chain, generating a web of opportunities and development, since it directly and indirectly affects other production chains. It becomes evident that government intervention, considering the programs aimed at housing, that the MCMV was the one that most expanded and strengthened housing assistance in all its spheres, revealing itself as a driving force of the economy, by generating jobs, income and circulation of products.